FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN LAYANAN VOLUNTARY COUNSELING AND TESTING (VCT) PADA IBU HAMIL DI PUSKESMAS KENALI BESAR KOTA JAMBI - Enny Susilawati; Ambo Sengngeng; Lia Artika Sari (NHM PRESS, 2021)
The use of VCT clinics is very important because it is the most important “entrance” to prevention, care, support and treatment services including prevention of mother-to-child transmission of HIV which is an important component of treatment with ARVs. The purpose of this study was to analyze the factors related to the behavior of using VCT services. This includes observational analytic research using a cross sectional study design. This research was conducted at the Kenali Besar Health Center, Jambi City in February-July 2019. This study involved 93 participants in the form of pregnant women who made antenatal visits, namely pregnant women in the 1st to 3rd trimesters. The instrument is a tool used to collect data. The type of instrument used in this study was a questionnaire sheet. Then the results of filling out the questionnaire were analyzed using a distribution table which was confirmed in the form of frequency distribution, percentage and narrative. The statistical test used was chi square at a significant value = 0.05. The use of VCT is related to knowledge (0.000), attitude (0.000), and service personnel (0.000). VCT utilization behavior will be carried out if knowledge is good, positive and has a good service role. It is hoped that health workers will increase public understanding of VCT services in the form of socialization and counseling.